Unraveling the selective antibacterial activity and chemical composition of citrus essential oils - Ambrosio C.M.S. (2019)
Post-weaning diarrhea (PWD) is an often disease affecting piglets. It is caused mainly by enterotoxigenic Escherichia coli (ETEC) colonization in pig gut. Antibiotics has been used to prevent, combat and control PWD and its negative impact on the productivity of pig breeding sector. Nonetheless, antibiotics due to their wide antibacterial spectrum also can reach beneficial gut bacteria, such as Lactobacillus. Lately, essential oils (EOs) have emerged as a potential alternative to using antibiotics in animal breeding because of their effect on bacterial growth. Commonly, citrus EOs are by-products of food industry and the availability of these EOs in the worldwide market is huge. Thus, six commercials citrus EOs were evaluated on ETEC strains, as model of pathogenic bacteria, and on Lactobacillus species, as models of beneficial bacteria. In overall, citrus EOs exhibited a selective antibacterial activity with higher effect on pathogenic bacteria (ETECs) than beneficial bacteria (Lactobacillus). Brazilian orange terpenes (BOT) oil presented the highest selective performance and caused higher disturbances on the normal growth kinetic of ETEC than on Lactobacillus rhamnosus. The action was dose-dependent on the maximal culture density (A) and the lag phase duration (λ) of the ETEC. The highest sub-inhibitory concentration (0.925 mg/mL) extended the λ duration to ETEC eight times (14.6 h) and reduced A in 55.9%. For L. rhamnosus, the λ duration was only extended 1.6 times. Despite the fact that limonene was detected as the major compound, the selective antibacterial activity of the citrus EOs could not be exclusively attributed to limonene since the presence of minor compounds could be implicated in conferring this feature. © 2019, The Author(s).